Wordsworth's "Tintern abbey" and the tradition of the "hymnal" ode - Sandro Jung (Acta Neophilologica, 2007)
Despite the claims for simplicity of language that Wordsworth articulated in the early years of his literary career, especially in the "Preface" to Lyrical Ballads-his pronounced difference from earlier (Neoclassical) poets, poetic practice, and the forms of poetry of the Augustans-he could not escape what Waiter Jackson Bate long ago termed the "burden of the past". Wordsworth's indebtedness to his literary forbears is not only ideational but formal as well. The present article aims to examine Wordsworth's "Tintern Abbey" and relate it to the tradition of the hymnal ode used so masterfully by William Collins in the mid-century, at the same time reconsidering the generic conceptualisation of the poem as an ode in all but name which in its structure and essence re-evokes mid-century hymnal odes but which is contextualised within Wordsworth's notion of emotional immediacy and simplicity.